Place of lactase deficiency in the pathogenesis of rotavirus infection and possibilities of its correction - E. V. Usachova; N. V. Tarasenko (Zaporožskij Medicinskij Žurnal)
Rotavirus infection is one of the causes of the lactase deficiency. The pathogenesis of the lactase deficiency in this disease has been actively studied recently. But the dynamic changes of clinical and laboratory signs of the lactase deficiency in early age children on the background of rotavirus infection and methods of their correction are still not well investigated.